A Polycarboxyl‐Decorated FeIII‐Based Xerogel‐Derived Multifunctional Composite (Fe3O4/Fe/C) as an Efficient Electrode Material towards Oxygen Reduction Reaction and Supercapacitor Application. Issue 25 (17th April 2018) - Devi, Bandhana; Venkateswarulu, Mangili; Kushwaha, Himmat Singh; Halder, Aditi; Koner, Rik Rani
Abstract: Low cost, non‐noble metal catalysts with a good oxygen reduction reaction (ORR) activity comparable to that of platinum and also having good energy storage properties are highly desirable but challenging. Several challenges are associated with the development of such materials. Herein, we demonstrate a new polycarboxyl‐functionalised Fe III ‐based gel material, synthesised following a solvothermal method and the development of its composite (Fe3 O4 /Fe/C) by annealing at optimised temperature. The developed composite displayed excellent electrocatalytic activity for the oxygen reduction reaction with an onset potential of 0.87 V (vs. RHE) and a current density value of −5 mA cm −2, which are comparable with commercial 20 wt % Pt/C. In addition, as one of the most desirable properties, the composite exhibits a better methanol tolerance and greater durability than Pt/C. The same material was explored as an energy storage material for supercapacitors, which showed a specific capacitance of 245 F g −1 at a current density of 1 A g −1 . It is expected that this Fe3 O4 /Fe/C composite with a disordered graphitised carbon matrix will pave a horizon for developing energy conversion and energy storage devices. Abstract : Two birds with one stone : A new Fe3 O4 /Fe/C composite material synthesised from a polycarboxyl‐decorated Fe III ‐based xerogel showed great potential to be applied as a catalyst in the oxygen reduction reaction as well as energy storage material for supercapacitor application (see figure).